On the Kantian distinction between Ethics and Right: Linearity and Mediation - Capasso, Marianna; Pirni, Alberto (Con-Textos Kantianos. International Journal of Philosophy, 2021)
The aim of this paper is to provide an original account of the distinction between the spheres of Sitten that goes beyond the traditional one based on the nature of incentives, since this underestimates some of their characteristics. First, the paper identifies in obligatio a common source between Ethics and Right. Then, it explores how in the Metaphysics of Morals the connection between law and incentive constitutes a more relevant criterion to distinguish ethical lawgiving from juridical lawgiving. Specifically, it demonstrates that such connection: (a) to be ethical should be linear, understood as a necessary self-determined process of connecting law to incentive; (b) to be juridical should be mediated, namely it comprises an inclusive disjunction between two modalities of connecting law to incentive: a non-necessary linear and a divergent one. It concludes by exploring the implications of such perspective on the notions of internalisation and externalisation associated to each lawgiving.